Identitas Gaya Hidup dan Budaya Konsumen dalam Mengkonsumsi Brand The Executive - Rafa'al, Mubaddilah (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2017)
Humans not only buy the needed goods, but also the brand. Brand goods are self-pride. Buying reputable brands creates a feeling of